Preparation method of PdMFe1-M bimetallic catalyst constructed by halloysite nanotube confinement and performance research of PdMFe1-M bimetallic catalyst for directly synthesizing H2O2 by using PdMFe1-M bimetallic catalyst
By the upper limit domain PD and FE in Ellow nano-pipe, the electronic state and lattice of the catalyst regulating the catalyst solves the problem of uneven particle size in the process of direct synthesis of H2O2 and the break of O-O. Essence
Patent Information
- Application Number
- CN202410961369.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-17
- Publication Date
- 2025-01-24
AI Technical Summary
During the direct synthesis of H2O2, Pd nanoparticles have uneven particle size and poor dispersion due to high surface energy, and lead to O-O bond fracture, resulting in a decrease in H2O2 yield and selectivity.
By using Ellow nano-pipe as a limited domain carrier, the PD and Fe restricted domain are used to the inside of nanopoastes, and the electronic status and lattice of the PD are regulated to inhibit the solution of O-O, thereby improving the synthesis efficiency of H2O2.
The high surface area and larger cavity structure of the catalyst PDMFE1-M/HNT are realized, reducing production costs, and significantly improved the catalytic performance of direct synthesis of H2O2, especially the yield and selectivity of H2O2.
Smart Images

Figure CN119346135A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of performance research on bimetallic catalysts for direct synthesis of H2O2, and specifically relates to a method for confining Pd M Fe 1-M Preparation method of bimetallic catalyst and its performance study for direct synthesis of H2O2. Background Art
[0002] The direct synthesis of hydrogen peroxide (H2O2) from hydrogen and oxygen is a green and economical method that has attracted much attention in recent years. Pd-based catalysts are commonly used catalysts for the direct synthesis of H2O2, but Pd nanoparticles are very easy to migrate and agglomerate during the preparation process due to their high surface energy, resulting in uneven particle size and poor dispersion. In addition, while catalyzing the synthesis of H2O2 from hydrogen and oxygen, Pd nanoparticles will cause the OO in oxygen-containing intermediate species (O2*, OOH* and HOOH*) to break and generate byproduct H2O, resulting in a decrease in the yield and selectivity of H2O2. Halloysite nanotubes (HNTs) are naturally occurring aluminosilicate clays. They are multi-walled nanotubes with a hollow structure and good crystallinity. The chemical formula is (Al2Si2O5(OH)4·nH2O). Its tubular structure is due to the mismatch between the inner and outer silicon oxygen tetrahedron layers and the aluminum oxygen octahedron layers in space, which causes the lattice to be misaligned and curled. And because the Al-OH group is protonated, it carries positive charge inside, while the Si-OH group is deprotonated, causing the outside of the pipe to carry negative charge. Using HNT as a confined carrier and H2PdCl4 as a metal precursor, the active component Pd can be confined to the interior of the HNT by utilizing the electrostatic interaction between the inner surface of the HNT and PdCl42-. Secondly, by incorporating cheap metal Fe with low electronegativity and small atomic radius, the electronic state and lattice of Pd are regulated, and the dissociation of OO is inhibited, thereby efficiently synthesizing H2O2.
[0003] To this end, we propose a method to confine Pd M Fe 1-M The preparation method of bimetallic catalysts and their performance in directly synthesizing H2O2 are studied to solve the above problems. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a preparation method of a PdMFe1-M bimetallic catalyst confined by halloysite nanotubes and a performance study of the catalyst for directly synthesizing H2O2.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A halloysite nanotube confined Pd M Fe 1-M-M bimetallic catalyst preparation method, comprising the following steps:
[0007] S1. Pretreatment of Halloysite Nanotubes:
[0008] The original halloysite nanotubes were placed in an oil bath with piranha solution at 90°C and condensed under reflux at 3°C for 1 hour. The precipitate was collected by centrifugation, then washed with deionized water several times until the pH was neutral, vacuum dried in a vacuum oven at 40°C for 12 hours, and finally taken out and ground for use. The pretreated halloysite was named HNT;
[0009] S2, catalyst Pd M Fe 1-M Preparation of HNT: The HNT in step S1 is placed in a beaker, and ultrapure water is added thereto. The HNT is evenly dispersed by ultrasonic cleaning in an ultrasonic cleaning machine for 20 minutes, and then placed on a magnetic stirrer. After heating it to 30°C, a 50wt% NaOH solution prepared in advance is used to adjust its pH to 12. Then, 128μl of a mixed solution of H2PdCl4 and FeCl3 with a concentration of 0.075M is drawn with a pipette and added dropwise to the above solution. The mixture is stirred at a constant temperature of 30°C for 1 hour, and the solution turns from white to orange-yellow. The precipitate is collected by centrifugation, washed with ultrapure water several times until the pH is neutral, and then placed in a vacuum drying oven and vacuum dried at 40°C for 12 hours. The final sample is taken out and ground, and then placed in a tube furnace and reduced with H2 for 2.5 hours to obtain the catalyst Pd M Fe 1-M M / HNT.
[0010] Furthermore, in step S1, the volume ratio of concentrated H2SO4 to H2O2 in the piranha solution is 7:3.
[0011] Another object of the present invention is to provide a method for confining Pd in a halloysite nanotube. M Fe 1-M The performance of bimetallic catalysts for direct synthesis of H2O2 was studied by analyzing the Pd confined structure of halloysite nanotubes prepared by the above method. M Fe 1-M The characterization of bimetallic catalysts was studied.
[0012] Furthermore, by analyzing the catalyst Pd M Fe 1-M The steps for characterization of HNT are as follows:
[0013] S1. Analysis of catalyst Pd M Fe 1-M / TEM characterization of HNTs;
[0014] S2. Analysis of catalyst Pd MFe 1-M / XRD characterization of HNTs;
[0015] S3. Analysis of catalyst Pd M Fe 1-M XPS characterization of M / HNT;
[0016] S4, catalyst Pd M Fe 1-M / HNT activity evaluation, using catalyst Pd M Fe 1-M / HNT activity to study the confined construction of Pd in halloysite nanotubes M Fe 1-M Performance of bimetallic catalysts for direct synthesis of H2O2.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The catalyst Pd prepared by the present invention M Fe 1-M / HNT has the characteristics of high surface area and large cavity structure, low production cost, and excellent catalytic performance for the direct synthesis of H2O2. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 For Pd / HNT and Pd0 0.7 Fe 0.3 / TEM image of HNT;
[0020] Figure 2 For Pd / HNT and Pd X -Fe Y / XRD spectrum of HNT;
[0021] Figure 3 For Pd / HNT and Pd M Fe 1-M / XPS full spectrum of HNT;
[0022] Figure 4 For Pd / HNT and Pd M Fe 1-M / HNT activity evaluation results. DETAILED DESCRIPTION
[0023] The following will describe the implementation methods of the present application in detail with the help of accompanying drawings and examples, so that the implementation process of how the present application uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly.
[0024] See also Figure 1-2 The present invention provides a method for confining Pd in halloysite nanotubes. MFe 1-M The preparation method of the bimetallic catalyst is as follows:
[0025] (1) Pretreatment of Halloysite Nanotubes
[0026] Weigh 3.000g of raw halloysite nanotubes, use 30.00ml of piranha solution (concentrated H2SO4 and H2O2 mixed in a volume ratio of 7:3) in an oil bath at 90℃, condense and reflux at 3℃ for 1 hour. Centrifuge to collect the precipitate, then wash it with deionized water several times until the pH is neutral. Vacuum dry it in a vacuum oven at 40℃ for 12 hours, finally take it out and grind it for use, and the pretreated halloysite is named HNT.
[0027] (2) Catalyst Pd M Fe 1-M Preparation of HNT
[0028] Preparation of Pd / HNT: Weigh 0.100g of the above HNT and place it in a 100ml beaker, add 40.00ml ultrapure water, and ultrasonicate it in an ultrasonic cleaning machine for 20 minutes to make it evenly dispersed. Then, place it on a magnetic stirrer, heat it to 30°C, use a 50wt% NaOH solution prepared in advance to adjust its pH to 12, then use a pipette to draw 128μl of a mixed solution of H2PdCl4 and FeCl3 with a concentration of 0.075M and add it dropwise to the above solution, stir it at a constant temperature for 1 hour at 30°C, and it can be seen that the solution turns from white to orange-yellow. Collect the precipitate by centrifugation, wash it several times with ultrapure water until the pH is neutral, place it in a vacuum drying oven, and vacuum dry it at 40°C for 12 hours. Take out the final sample, grind it, and place it in a tube furnace to reduce it with H2 for 2.5h to obtain the catalyst Pd / HNT.
[0029] For Pd M Fe 1-M The performance of bimetallic catalysts for direct synthesis of H2O2 was studied by analyzing the Pd confined structure of halloysite nanotubes prepared by the above method. M Fe 1-M The characterization of bimetallic catalysts was studied.
[0030] Catalyst Pd M Fe 1-M TEM characterization of HNTs
[0031] In order to fully understand the catalyst Pd / HNT and Pd M Fe 1-M / HNT morphology and size, TEM characterization analysis was used to analyze the morphology and size of the catalyst. Figure 4 For Pd / HNT and Pd 0.7 Fe 0.3 / HNT TEM characterization results, first, as Figure 4 As shown in (a) and (c), the tube structure of the pretreated carrier HNT remains intact, indicating that the pretreatment process does not destroy the structure of the nanotube itself. In addition, it can be clearly seen that the Pd nanoparticles are evenly distributed inside the HNT tube, indicating that the Pd and Pd 0.7 Fe 0.3 Alloy particles are confined to the interior of HNT. Catalyst Pd / HNT and Pd 0.7 Fe 0.3 Pd and Pd / HNT 0.7 Fe 0.3 The particle size distribution of nano alloy particles is as follows Figure 4 As shown in (b) and (d), the Pd particles and Pd 0.7 Fe 0.3 The average sizes of the alloy particles are 2.74nm±0.06nm and 2.96nm±0.2nm, respectively. The size distribution of the active metal particles is extremely narrow, indicating that the inner surface charge properties of the carrier one-dimensional nanotube HNT play a decisive role in the distribution of Pd particles, and the introduction of the second metal Fe does not have a significant effect on the particle size of Pd nanoparticles.
[0032] See also Figure 1 , (e) is the HRTEM image of Pd nanoparticles, it can be clearly seen that Pd 0.7 Fe 0.3 The alloy nanoparticles have an oriented crystal structure with a surface lattice spacing of 0.221 nm, which is slightly smaller than the spacing of the face-centered cubic crystal type of Pd (111) (0.224 nm). This is because the atomic radius of Fe is smaller than that of Pd. 0.7 Fe 0.3 The alloy particles produce compressive strain, which enhances the adsorption of Pd 0.7 Fe 0.3 The bond energy of OO on the alloy particles reduces the possibility of their breaking, which can effectively improve the H2O2 selectivity. Figure (f) shows the catalyst Pd 0.7 Fe 0.3 / SEM image of HNT, Figure 4 (g) to (k) are the corresponding element distribution diagrams. The results show that Pd and Fe exist simultaneously and are evenly distributed, proving that Pd 0.7 Fe 0.3 Successful synthesis of the alloy.
[0033] Figure 1 In the figure, (a) and (c) are Pd / HNT and Pd 0.7 Fe 0.3 / HNTTEM images; (b) and (d) are Pd / HNT and Pd0.7 Fe 0.3 / HNT Pd nanoparticle size statistics; (e) Pd 0.7 Fe 0.3 HRTEM image of / HNT; (fk)Pd 0.7 Fe 0.3 / HNT SEM image and EDS surface scan.
[0034] Catalyst Pd M Fe 1-M XRD characterization of HNT
[0035] See also Figure 2 First, it can be seen that the XRD peaks of all samples showed typical HNT characteristic peaks at 2θ=12.2°, 19.9°, 24.4°, 26.6°, 38.5°, 55.2°, 62.5°, 73.9° and 77.4, indicating that the pretreatment process did not affect the crystal structure of HNT. The XRD patterns of all samples showed relatively blunt Pd diffraction characteristic peaks at 2θ=40.1°, 46.6°, 68.1° and 82.1°. However, the catalysts Pd / HNT and Pd M Fe 1-M There are no obvious lattice diffraction characteristic peaks of Pd and Fe in / HNT, which means that the crystallinity of the metal and alloy particles in the catalyst is lower or the particle size is too small. According to the TEM results, Pd and PdFe alloy particles are loaded inside the halloysite nanotubes. The relatively low intensity of Pd characteristic peaks may be attributed to the shielding of amorphous halloysite walls. On the other hand, combined with the TEM characterization results, it can be seen that Pd / HNT and Pd 0.7 Fe 0.3 The particle sizes of Pd nanoparticles of / HNT are about 2.74nm and 2.96nm, respectively, and the particle dispersion is very good. It is difficult for such small-sized nanocrystals to show obvious diffraction peaks.
[0036] Catalyst Pd M Fe 1-M XPS characterization of HNT
[0037] In order to understand the surface element state of the catalyst Pd / HNT and the effect of adding metal Fe on the catalyst Pd M Fe 1-M The influence of the Pd electronic state of the catalyst Pd / HNT and Pd / HNT was analyzed by XPS. M Fe 1-M / HNT chemical state information and surface composition elements, the results are as follows Figure 3 shown. Figure 3 (a) Pd / HNT and Pd M Fe1-M / HNT full XPS spectrum, the figure clearly shows the characteristic peaks of Al 2p, Si 2p and O1s in the HNT carrier, the Pd 3d characteristic peak is not particularly obvious, and no obvious Fe 2p characteristic peak is seen. There may be two reasons for this. On the one hand, since XPS characterization is a surface analysis technology, combined with the TEM characterization results, it is speculated that since Pd and Fe particles only exist inside the lumen of HNTd, XPS surface analysis is difficult to detect elements inside the material, which is the fundamental reason for the weak Pd and Fe characteristic peaks. On the other hand, it may be that the total catalyst metal loading is only 1%, and the highest proportion of Fe in the molar ratio of the total metal is only 40%, resulting in XPS only scanning the Pd 3d characteristic peak and difficulty in detecting the presence of Fe.
[0038] Therefore, only the Pd 3d spectrum is analyzed. Figure 3 (b) shows Pd / HNT and Pd M Fe 1-M The Pd3d spectrum analysis results of / HNT show that the two peaks appearing in all catalysts can be fitted into four peaks, among which the peaks near 335.4eV and 340.5eV can be attributed to Pd 0 3d 5 / 2 and Pd 0 3d 3 / 2 , while the peaks near 336.2eV and 341.6eV can be attributed to Pd 2+ 3d 5 / 2 and Pd 2+ 3d 3 / 2 It is worth noting that after adding metallic Fe, Pd 0 3d 5 / 2 The characteristic peak of Pd 0 3d 5 / 2 The degree of shift of the characteristic peak increases with the increase in the proportion of added Fe. This is mainly attributed to the increase in the electron density of Pd, because the electronegativity of Pd (2.2) is greater than that of Fe (1.8), resulting in the transfer of electrons from Fe to Pd. In the direct synthesis of hydrogen peroxide, the reduction in the XPS binding energy of Pd is conducive to weakening the adsorption of O2 by the active center, which can weaken the breakage of OO to a certain extent and play a role in improving the selectivity of H2O2. It is worth mentioning that according to the results of the Pd 3d characteristic peak fitting, the catalysts Pd / HNT and Pd M Fe 1-M Pd in HNT 0 and Pd 2+ The relative content of Figure 4As shown in (c), it is found that after the introduction of the second metal Fe, the electron transfer from Fe to Pd leads to the reduction of Pd in the catalyst. 0 The relative content of Pd increases, and the upward trend is positively correlated with the proportion of Fe. Studies have shown that 0 The presence of is conducive to promoting the adsorption of H2. There is no doubt that the introduction of Fe to prepare the Pd-Fe bimetallic catalyst is extremely beneficial for increasing the H2O2 yield.
[0039] Figure 3 (a) Pd / HNT and Pd M Fe 1-M / HNT; (b) Pd / HNT and Pd M Fe 1-M / HNT Pd 3d spectrum; (c) catalyst Pd / HNT and Pd M Fe 1-M Pd in HNT 0 / Pd 2+ ratio.
[0040] Catalyst Pd M Fe 1-M / HNT activity evaluation
[0041] For catalysts Pd / HNT and Pd M Fe 1-M / HNT was used to evaluate the catalytic performance of direct synthesis of H2O2. Figure 4 As shown, it can be found that the H2O2 yield of the catalyst Pd / HNT is 3851mmol / g Pd ·h -1 After the introduction of Fe, the bimetallic catalyst Pd M Fe 1-M The H2O2 yield of the catalyst Pd / HNT showed an upward trend, and the various performance indicators showed an obvious volcanic change trend with the increase of Fe content. When the molar ratio of Pd:Fe was 0.7:0.3, the catalyst Pd 0.7 Fe 0.3 / HNT has the best performance indicators. Its H2O2 yield and selectivity reached 5606mmol / g Pd ·h -1 and 82.9%, with Pd / HNT (3851mmol / g Pd ·h -1 and 68.8%), respectively, which were increased by 46% and 20.5%. It is speculated that the introduction of Fe can increase the isolated Pd sites, increase the exposed active sites, and promote the increase of H2O2 yield. In addition, according to the TEM characterization results, Pd 0.7 Fe 0.3The alloy particles undergo compressive strain, which increases the bond energy of OO and reduces the possibility of its breakage, which can effectively improve the selectivity of H2O2. The XPS results show that the introduction of Fe metal increases the Pd 0 The ratio of Pd to Fe can increase the H2O2 yield of the catalyst, and the Pd binding energy shift can reduce the adsorption of O2 by Pd nanoparticles to a certain extent, thereby preventing the breakage of the OO bond and further increasing the selectivity. However, when the Pd:Fe ratio is 0.6:0.4, the increase in Fe content causes the Pd binding energy to shift too much, which greatly reduces its adsorption of O2, resulting in a decrease in H2 conversion and ultimately a decrease in H2O2 yield.
[0042] Figure 4 (a) Catalyst Pd / HNT and Pd M Fe 1-M / HNT; (b) the H2O2 yield of catalysts Pd / HNT and Pd M Fe 1-M / HNT H2O2 selectivity; (c) catalyst Pd / HNT and Pd M Fe 1-M / HNT; (d) catalyst Pd / HNT and Pd M Fe 1-M / H2O2 yield of HNT.
[0043] Using the one-dimensional material halloysite nanotube HNT with a large cavity structure and positively charged inside the tube as a carrier of Pd, the charge properties of its inner surface were used to successfully confine Pd particles to the inside of the HNT tube to prepare the catalyst Pd / HNT. On this basis, the cheap metal Fe was further introduced as the second metal to prepare a series of bimetallic catalysts Pd M Fe 1-M / HNT. The effect of carrier HNT on the catalytic performance of Pd / HNT catalyst for direct synthesis of H2O2 was studied, and the effect of the ratio of introduced Fe on the electronic state of Pd surface and the catalytic performance of the catalyst for direct synthesis of H2O2 was further explored. The following conclusions were drawn:
[0044] (1) TEM characterization results show that the active metal Pd is confined to the interior of the HNT tube, and the Pd nanoparticles are evenly distributed with an average particle size of only 2.74 nm. EDS scanning proves the successful introduction of the second metal Fe, and the Pd synthesized by the bimetallic catalyst 0.7 Fe 0.3 The alloy particle size (2.96 nm) changed only slightly, but due to the 0.7 Fe 0.3The alloy particles undergo compressive strain, and their lattices are slightly smaller than those of Pd. XRD characterization results show that the characteristic peaks of Pd and Fe are not obvious, which further confirms that HNT converts Pd and Pd 0.7 Fe 0.3 The alloy particles were successfully confined to the interior. XPS characterization results show that the addition of metal Fe regulates the surface electronic state of Pd. Since the electronegativity of Fe is less than that of Pd, Fe will transfer electrons to Pd, resulting in the bimetallic catalyst Pd X -Fe Y Pd in HNT 0 The relative content of Pd increases, while the binding energy of Pd decreases.
[0045] (2) The catalytic performance of the catalyst for direct synthesis of H2O2 was evaluated. The addition of the second metal Fe had a favorable effect on the catalytic performance of direct synthesis of hydrogen peroxide. The catalytic performance was best when the ratio of Pd to Fe was 7:3. This is because the introduction of Fe made Pd 0.7 Fe 0.3 The alloy particles produce compressive strain, and at this time the catalyst Pd 0.7 Fe 0.3 Pd in HNT 0 / Pd 2+ The ratio of is most suitable, which can provide enough active sites, increase the H2O2 yield, and inhibit the breakage of the OO bond in the hydrogen peroxide reaction, resulting in its excellent H2O2 selectivity.
[0046] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any simple modifications or equivalent changes made to the above embodiments based on the technical essence of the present invention fall within the protection scope of the present invention.
[0047] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are within the scope of the technical solution of the present invention.
Claims
1. A Halloysite Nanotube Confined Pd M Fe 1-M A method for preparing a bimetallic catalyst, characterized in that: The following steps are involved: S1. Pretreatment of Halloysite Nanotubes: The original halloysite nanotubes were placed in an oil bath with piranha solution at 90°C and condensed under reflux at 3°C for 1 hour. The precipitate was collected by centrifugation, then washed with deionized water several times until the pH was neutral, vacuum dried in a vacuum oven at 40°C for 12 hours, and finally taken out and ground for use. The pretreated halloysite was named HNT; S2, catalyst Pd M Fe 1-M Preparation of HNT: The HNT in step S1 is placed in a beaker, and ultrapure water is added thereto. The HNT is evenly dispersed by ultrasonic cleaning for 20 minutes in an ultrasonic cleaning machine, and then placed on a magnetic stirrer. After heating it to 30°C, a 50wt% NaOH solution prepared in advance is used to adjust its pH to 12. Then, 128μl of a mixed solution of H2PdCl4 and FeCl3 with a concentration of 0.075M is drawn with a pipette and added dropwise to the above solution. The mixture is stirred at a constant temperature of 30°C for 1 hour. The solution turns from white to orange-yellow. The precipitate is collected by centrifugation, washed with ultrapure water several times until the pH is neutral, and then placed in a vacuum drying oven and vacuum dried at 40°C for 12 hours. The final sample is taken out and ground, and then placed in a tube furnace and reduced with H2 for 2.5 hours to obtain the catalyst Pd M Fe 1-M / HNT.
2. The halloysite nanotube confined construction of Pd according to claim 1 M Fe 1-M A method for preparing a bimetallic catalyst, characterized in that: In step S1, the volume ratio of concentrated H2SO4 to H2O2 in the piranha solution is 7:
3.
3. The halloysite nanotube confined construction of Pd according to claim 1 M Fe 1-M A method for preparing a bimetallic catalyst, characterized in that: The molar ratio of Pd to Fe in the mixed solution of H2PdCl4 and FeCl3 is M:1-M, where M=0.9, 0.8, 0.7 and 0.
6.
4. A Halloysite Nanotube Confined Pd M Fe 1-M The performance of bimetallic catalysts for direct synthesis of H2O2 is studied, characterized by: Halloysite nanotube confined construction of Pd prepared according to any one of claims 1 to 3 M Fe 1-M Bimetallic catalysts, by analyzing the catalyst Pd M Fe 1-M / HNT characterization was carried out to study.
5. The halloysite nanotube confined construction of Pd according to claim 4 M Fe 1-M The performance of bimetallic catalysts for direct synthesis of H2O2 is studied, characterized by: By analyzing the catalyst Pd M Fe 1-M The steps for characterization of HNT are as follows: S1. Analysis of catalyst Pd M Fe 1-M / TEM characterization of HNTs; S2. Analysis of catalyst Pd M Fe 1-M / XRD characterization of HNT; S3. Analysis of catalyst Pd M Fe 1-M / XPS characterization of HNT; S4, catalyst Pd M Fe 1-M / HNT activity evaluation, using catalyst Pd M Fe 1-M / HNT activity to study the confined construction of Pd in halloysite nanotubes M Fe 1-M Performance of bimetallic catalysts for direct synthesis of H2O2.